PENGARUH PENGGUNAAN GOOGLE CLASSROOM DAN WHATSAPP TERHADAP HASIL BELAJAR GEOGRAFI KELAS XI IPS DI SMA NEGERI 1 DUMAI - Siregar, Adilla Santi; Rahmanelli, Rahmanelli (JURNAL BUANA, 2023)
One of the technological advances is the use of the internet in Learning Management Systems, such as google classroom and whatsapp to overcome the implementation of online learning. The purpose of this study was to determine the effect of the use of google classroom and whatsapp on the learning outcomes of geography in the even semester of class XI IPS at SMA Negeri 1 Dumai. The research method is quantitative with an associative approach. The sampling technique was random sampling, totaling 78 students. Data collection techniques by means of tests, questionnaires, and documentation. Data analysis techniques with multiple linear regression, classical assumption test, and hypothesis testing (t test and f test). The results of the study partially prove that the use of google classroom (X1) has a significant and positive effect of 0.581, and whatsapp (X2) has a significant and positive effect of 1.451 on the learning outcomes of geography (Y) class XI IPS at SMA Negeri 1 Dumai. The results of the simultaneous acquisition are the calculated F value 13.62 > F table 1.94, and judging from the significant probability value 0.262 < 0.05, Ho is rejected and Ha is accepted. Overall, the use of google classroom and whatsapp has an effect on geography learning outcomes by 93.2% while the difference is 6.8% by other variables.